When work and family collide: a phenomenological Inquiry exploring work-family conflicts among professional working mothers at institutions of higher education / Siti Kamalia Sabri and Syarifah Rohaniah Syed Mahmood - Sabri, Siti Kamalia; Syed Mahmood, Syarifah Rohaniah (Universiti Teknologi MARA, Sabah, 2025)
Democratization in the education system and changes in social norms significantly expanded the roles of women in Malaysia. As the nation modernized, professional working mothers faced escalating demands, highlighting the necessity for a deeper understanding of the work-family dynamic. Balancing professional and domestic roles often resulted in work-family conflict, where competing demands were incompatible. The purpose of this phenomenological study is to explore experiences of professional working mothers at Institutions of Higher Education (IHE) with particular emphasis on specific conflicts in balancing work and family. In-depth interviews were conducted with six (6) informants selected through snowball sampling technique. The data were analyzed using Atlas.ti9 and van Kaam method was modified, which included seven steps such as horizontalization, reduction and elimination, clustering and thematizing invariant constituents, validating themes, and constructing textual-structural descriptions. The findings revealed three themes related to psychological experiences of the professional working mothers such as barriers in personal life, family matters and work-related challenges.